Aplikasi Virtual Tour Rumah Adat Saoraja Kabupaten Pinrang - Budianti, Ayu Ningrum; Pawelloi, A. Irmayani; Wafiah, Andi (KOMPUTEK, 2025)
Pinrang Regency has the Saoraja Traditional House as one of the cultural heritages that is still preserved. However, the lack of information and use of technology in introducing this traditional house has caused the community to be less familiar with it. This study aims to design and build a Virtual Tour application based on Virtual Reality (VR) to provide an interactive exploration experience of the Saoraja Traditional House. The methods used in this study include literature studies, observations, and software development with object-based models. The application was developed using Unity as the main platform and SketchUp for 3D object modeling. Testing was carried out using the Black Box and White Box methods to ensure that the application functionality runs according to the expected specifications. The results of the study show that this Virtual Tour application can display 3D visualization of the Saoraja Traditional House with realistic interactions using VR Box and users can explore the inside of the traditional house to obtain historical information digitally